2000
DOI: 10.1111/j.1151-2916.2000.tb01510.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Texture Analysis Techniques for Highly Oriented α‐Al2O3

Abstract: Texture measurements were performed on liquid-phasesintered alumina textured by a templated grain growth process from 1250°to 1650°C. Texture distributions were measured using X-ray pole figures, rocking curves, Rietveld refinement, and stereology. The March-Dollase equation fitted the measured distributions very well and gave quantitative values of the degree of texture and the texture fraction. The fitting parameters of the X-ray diffraction measurements were comparable to those measured by stereology. Rocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 19 publications
2
67
0
Order By: Relevance
“…Among the various methods discussed, the quantitative texture analysis techniques include pole figure analysis, EBSD, Rietveld refinement, and the rocking-curve method. Nevertheless, in several studies, it has been suggested that the XRD rocking-curve method is the most time-efficient and accurate texture analysis technique, as demonstrated for Al 2 O 3 [118] and PMN-28 PT [119] ceramics.…”
Section: Electron Backscattered Diffraction (Ebsd) Methodmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the various methods discussed, the quantitative texture analysis techniques include pole figure analysis, EBSD, Rietveld refinement, and the rocking-curve method. Nevertheless, in several studies, it has been suggested that the XRD rocking-curve method is the most time-efficient and accurate texture analysis technique, as demonstrated for Al 2 O 3 [118] and PMN-28 PT [119] ceramics.…”
Section: Electron Backscattered Diffraction (Ebsd) Methodmentioning
confidence: 99%
“…In addition to the above texture analysis methods, other methods, such as the Rietveld refinement and the XRD rocking-curve method [117], can also be applied to β-Si 3 N 4 ceramics [118,119]. Each method has its own strengths and weaknesses.…”
Section: Electron Backscattered Diffraction (Ebsd) Methodmentioning
confidence: 99%
“…As discussed with more detail in Section 5, our results indicate that the predicted magnitude of texture is larger than what is measured for a given amount of uniaxial stretch, λ. Seabaugh et al [54] used a weighted March-Dollase expression in which it is assumed the orientation of a volume fraction of particles, 1 − w, is unaffected by the deformation, thus resulting in a weighting of the initial and March pole densities, i.e.,…”
Section: Modified March Theorymentioning
confidence: 99%
“…Scanning electron microscopy (SEM) micrographs of //-cut samples were used to characterize the morphological texture. Crystallographic orientation distribution was obtained from corrected rocking-curve (or -scan) measurements, 5,6 using the (002) SBN53 peak. The orientation distribution was calculated by fitting corrected rocking curves to the March-Dollase equation:…”
Section: Methodsmentioning
confidence: 99%